Challenging elite environmentalism: Stories from Brazil and India - Ritodhi Chakraborty; Aline Carrara (Geo: Geography and Environment, 2025)
Abstract Elite environmentalism is inspired by Malthusian overpopulation scenarios, advocating for authoritarian action through top‐down conservation policies and celebrating ecomodernist climate adaptation/mitigation projects. In doing so, hegemonic mainstream environmentalism (HME) fails to address its colonial, authoritarian, saviorist foundations, which continue to motivate much of environmentalism. But there are also ongoing challenges to this by the work of Indigenous, feminist, anti‐racist, anti‐casteist, anti/de/post‐colonial thinkers and doers. In this work, we build upon such provocations, and through ethnographic stories of non‐elite communities, envision an alternative to HME. We propose a temporary analytical frame that advocates for non‐elite visions of environmentalism—non‐elite and more‐than‐colonial environmentalisms (NEMCEs). We witness the labour and aspirations of non‐elite communities (Indigenous and peasant) from Mato Grosso, Brazil, and Uttarakhand, India, as they pursue lives of defiance and dignity. Their stories reveal the unresolved contradictions at the heart of the capitalist, colonial and scientific worldview. Exploring the contentious identity positions of caste, class, indigeneity and gender, we examine land‐use change and ecological governance with the A'uwe Indigenous community in the agrarian heartland of the Brazilian cerrado and with lower‐caste agrarian families navigating the powerful manifestations of Hindu nationalism and neoliberal territorial management in the Indian Himalayas. These stories help us present a response to HME. They challenge its insidious reproduction of certain elite aspirations and institutions while claiming to support planetary visions of ecological well‐being. Additionally, these moments of non‐elite agency provide moments of hope.